MiR-125b Suppresses Proliferation and Invasion by Targeting MCL1 in Gastric Cancer. (4th October 2015) - Wu, Shihua; Liu, Feng; Xie, Liming; Peng, Yaling; Lv, Xiaoyuan; Zhu, Yaping; Zhang, Zhiwei; He, Xiusheng
Abstract : Understanding the molecular mechanisms underlying gastric cancer progression contributes to the development of novel targeted therapies. In this study, we found that the expression levels of miR-125b were strongly downregulated in gastric cancer and associated with clinical stage and the presence of lymph node metastases. Additionally, miR-125b could independently predict OS and DFS in gastric cancer. We further found that upregulation of miR-125b inhibited the proliferation and metastasis of gastric cancer cells in vitro and in vivo. miR-125b elicits these responses by directly targeting MCL1 (myeloid cell leukemia 1), which results in a marked reduction in MCL1 expression. Transfection of miR-125b sensitizes gastric cancer cells to 5-FU-induced apoptosis. By understanding the function and molecular mechanisms of miR-125b in gastric cancer, we may learn that miR-125b has the therapeutic potential to suppress gastric cancer progression and increase drug sensitivity to gastric cancer.